One–pot Selective Dihydroxylation of Limonene Combining Metal and Enzyme Catalysis. Issue 8 (14th June 2016) - Palumbo, Chiara; Ferrandi, Erica E.; Marchesi, Carlotta; Monti, Daniela; Riva, Sergio; Psaro, Rinaldo; Guidotti, Matteo
Abstract: A one‐pot sequential epoxidation‐hydrolysis reaction was developed by a combination of heterogeneous chemical and enzymatic catalysis, resulting in the selective dihydroxylation of (+)‐ and (‐)‐limonene. Highly enantioenriched 1, 2‐diols were obtained with good overall yields by applying a titanium‐grafted silica catalyst and the enzyme limonene 1, 2‐epoxide hydrolase, with no need to purify the reaction intermediate or to tune the reaction conditions to the enzymatic step. Abstract : A chemo–enzymatic marriage. A heterogeneous epoxidation catalyst based on Ti‐SiO2 is successfully combined with a limonene epoxide hydrolase enzyme in the one‐pot preparation of limonene‐1, 2‐diol. The complete compatibility between the metal and the enzymatic systems leads to the desired 1, 2‐diol with remarkable stereoconvergence and productivity.